Virtual Mirrors: Non-Line-of-Sight Imaging Beyond the Third Bounce - Royo, Diego; Sultan, Talha; Muñoz, Adolfo; Masumnia-Bisheh, Khadijeh; Brandt, Eric; Gutierrez, Diego; Velten, Andreas; Marco, Julio (Jornada de Jóvenes Investigadores del I3A, 2023)
Non-line-of-sight (NLOS) imaging methods reconstruct scenes hidden around one corner using indirect third-bounce illumination on a visible relay surface. We show how diffuse hidden objects may exhibit specular behaviour in NLOS methods, and how fourth- and fifth-bounce illumination can encode useful information, such as imaging objects hidden around two corners.